Endodontic Treatment of C-shaped Mandibular Premolars: A Case Report and Review of Literature - Khorasani, Monire; Nabavi, Saideh; Hamedi, Ali; Jafarzadeh, Hamid (Iranian Endodontic Journal, 2021)
Our article aimed to present a curious case of a mandibular premolar with a C-shaped root canal and to review the available literature on this anatomical variation. Mandibular premolar teeth account for the greatest endodontic challenges in the course of treatment on account of the morphological variations in their root canal systems, including extra root(s)/canal(s) or a C-shaped configuration. A 20-year-old female patient was referred to the Department of Endodontics of Mashhad Faculty of Dentistry, suffering from abscess, and pain while chewing. On examination the culprit was found to be the left mandibular first premolar. Following special tests and periapical radiography, we found an amalgam restoration proximate to the non-vital pulp chamber, as well as an unusually complex root canal anatomy with periapical radiolucency. A non-surgical root canal treatment with the aid of a dental operating microscope was considered as the treatment plan. Clinicians should always anticipate the presence of a C-shaped configuration in mandibular premolars, and make use of all the available tools to locate and treat such cases. A substantial knowledge of root canal anatomy would be prudent to ensure a successful outcome ensuing surgical and non-surgical root canal treatments.